Far-right and digital media: aesthetics, activism and discursive formations - Afouxenidis, Alex; Petridis, Petros (The Greek Review of Social Research, 2021)
This paper presents the relationship between the far-right and digital media in Europe and the USA. The article is a synthesis of key positions in the literature examining this relationship and some research observations concerning the Greek context. Although specific far-right rhetoric on issues such as nation, race, gender and sexuality are not new, they were communicated in new ways via social media. Digital technologies have not only provided opportunities for far-right networks to come together and publicize their message to larger audiences, but have also contributed to the internationalization of far-right positions and made their message more popular, resulting in an anti-systemic profile with a significant impact on activism in public spaces.